The influence of consumer perception, product quality, and brand image on purchasing decisions of pixy products in Batam city - Rahmadila Novi; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2026)
This study examines the influence of consumer perception, product quality, and brand image on purchasing decisions for Pixy products in Batam City. The research applied a quantitative survey approach using questionnaires distributed to 119 respondents who had purchased or used Pixy products. Data were analyzed using multiple linear regression with the assistance of SPSS 25. The findings indicate that consumer perception, product quality, and brand image each have a positive and significant effect on purchasing decisions. Consumer perception was influenced by product accessibility, service quality, product completeness, and price suitability, while product quality was reflected through performance, safety, reliability, and conformity with consumer expectations. Brand image also contributed significantly by strengthening consumer trust and confidence in Pixy products. Simultaneously, all independent variables significantly influenced purchasing decisions, with the coefficient of determination showing that the model explained 63.8% of the variation in purchasing decisions. The study concludes that improving positive consumer perception, maintaining product quality, and strengthening brand image are important strategies for increasing consumer purchasing decisions in the competitive cosmetic industry.